Zakat Profesi Persoalan Yuridis Di Indonesia dan Doktinal Dalam Islam - Mustatho, Mustatho (Ekonomi Syariah STAI Sangatta Kutai Timur, 2020)
The obligation to pay zakat in Islam is a very principle thing. This is because zakat contains two equally significant values, namely theological and social-economic values. The theological value of zakat is shown that zakat is a religious teaching that is obligatory and must be believed to be true. The commandments of zakat can be found in many places in the Qur'an. At least 32 verses of the Koran that call for zakat are found, including those that juxtapose the issue of zakat with the obligation to pray. In relation to socio-economic and social values, zakat can be an alternative solution to reduce the gap between the poor and the rich. The rich are responsible for the poor. This accountability in the language of the Qur'an Surah az-Zariyat verse 19 states that in the wealth of the rich there are rights for the poor and those in need.